Fiber-reinforced building solid waste recycled aggregate concrete and preparation method thereof

By performing nano-silica surface treatment on polypropylene fibers and combining modified graphene oxide, the shortcomings of concrete performance improvement and sustainable development in the existing technology are solved, and the high performance of fiber-reinforced construction solid waste recycled aggregate concrete is achieved. and durability improvement.

CN119430781AInactive Publication Date: 2025-02-14SHANDONG UNIV OF TECH

Patent Information

Application Number
CN202510049270.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving concrete performance and sustainable development, especially in the use of construction solid waste recycled aggregates and fiber reinforcement technologies, it is difficult to simultaneously improve the mechanical properties and durability of concrete.

Method used

The polypropylene fiber is surface coated with nano silica and combined with modified graphene oxide. By combining the interface between the modified fiber and concrete and modifying the conjugated structure of graphene oxide, the bond between fiber and concrete is improved. Force and conductivity of concrete.

Benefits of technology

It significantly improves the crack resistance, flexural strength, permeability, frost resistance and durability of fiber-reinforced construction solid waste recycled aggregate concrete, and enhances its mechanical properties and early strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430781A_ABST
    Figure CN119430781A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete preparation, in particular to fiber-reinforced building solid waste recycled aggregate concrete and a preparation method thereof.The preparation method comprises the following preparation steps that S1, recycled coarse aggregate, slag, fly ash and river sand are mixed and stirred according to the proportion, and a cement mixture is obtained; s2, calcining the cement mixture for 2-3 hours to obtain cement clinker; s3, cement clinker, modified fibers, modified graphene oxide and tetrasodium iminodisuccinate are mixed according to the proportion and then poured into a stirrer to be stirred for 5-6 min; and S4, adding water into the stirrer according to the proportion, continuously stirring for 6-10 minutes, and taking out to obtain the fiber-reinforced building solid waste recycled aggregate concrete. According to the invention, the polystyrene fiber and the concrete are connected more tightly by using the modified fiber, and the polystyrene fiber can be subjected to multiple reactions with components in the concrete in an alkaline environment of the concrete to form a stable network structure, so that mechanical indexes such as crack resistance and breaking strength of the concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, in particular to a fiber-reinforced construction solid waste recycled aggregate concrete and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization and the continuous advancement of infrastructure construction, the demand for natural resources such as natural sand and gravel is growing. However, excessive exploitation of natural sand and gravel will not only lead to resource depletion, but also cause serious damage to the ecological environment. For example, large-scale exploitation of river sand will destroy the river ecosystem and affect the living environment of aquatic organisms, and the exploitation of mountain rocks will destroy mountain vegetation and cause geological disasters such as landslides. Recycled coarse aggregate mainly comes from construction waste, such as waste concrete, waste bricks, etc. Processing these construction wastes into recycled coarse aggregate for concrete production realizes the recycling of resources. In the process of demolition of old buildings in cities, a large number of concrete blocks will be generated. These concrete blocks can be used as recycled coarse aggregate after crushing, screening and other treatments, reducing the exploitation of natural sand and gravel. According to statistics, for every ton of recycled coarse aggregate used, the exploitation of natural sand and gravel can be reduced by about 1.5-2 tons, which is of great significance for protecting natural resources and the ecological environment. The landfill of construction waste will occupy a lot of land resources and may pollute the soil and groundwater. The use of recycled coarse aggregate can effectively reduce the landfill of construction waste. Take a large-scale building demolition project as an example. If it is not recycled, the construction waste generated may need to occupy tens of thousands of square meters of landfill. Through recycling, these wastes can be converted into valuable building materials, thus greatly reducing the pressure on landfills.

[0003] In the field of concrete technology, continuously improving the performance of concrete to meet the needs of various complex engineering projects is the focus of research. Fiber reinforcement technology is one of the effective means to improve the performance of concrete. Fibers can play a role in strengthening and toughening concrete and improve the mechanical properties of concrete. Graphene oxide has excellent physical and chemical properties, such as high strength, high toughness and good conductivity. After modification, its application in concrete is expected to further improve the performance of concrete. At the same time, the development of new concrete preparation methods and additives to improve the durability, crack resistance and other properties of concrete is also one of the hot research directions. The present invention aims to provide a fiber-reinforced construction solid waste recycled aggregate concrete and a preparation method thereof to solve the problems existing in the prior art and promote the sustainable development of the field of building materials. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a fiber-reinforced construction solid waste recycled aggregate concrete and a preparation method thereof. The surface of polypropylene fiber is treated with nano-silicon dioxide. Nanomaterials have high specific surface area and special physical and chemical properties. A layer of nano-silicon dioxide coating is attached to the surface of polypropylene fiber to improve the interface bonding between polypropylene fiber and concrete matrix, and nano-silicon dioxide can react with calcium hydroxide in concrete to form chemical bonds, thereby improving the bonding force between fiber and concrete.

[0005] To achieve the above object, the present invention provides the following technical solutions: A fiber-reinforced construction solid waste recycled aggregate concrete comprises the following components by mass: 150-200 parts of recycled coarse aggregate, 170-230 parts of slag, 300-350 parts of fly ash, 180-230 parts of water, 10-25 parts of modified fiber, 2-10 parts of modified graphene oxide, 300-460 parts of river sand, and 10-30 parts of tetrasodium iminodisuccinate.

[0006] Preferably, the preparation of the modified fiber comprises the following steps: S11. 10-13 parts of nano-silicon dioxide and 1-3 parts of sodium hexametaphosphate are added to 60-80 parts of anhydrous ethanol and ultrasonically treated for 30-40 min to obtain a nano-silicon dioxide dispersion; S12. Add 15-17 parts of polypropylene fiber and 1-3 parts of organic silane coupling agent to the nano-silicon dioxide dispersion, stir at a speed of 700-800 r / min for 20-25 min, take out and dry to obtain modified fiber.

[0007] Preferably, the organic silane coupling agent is one of γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0008] Preferably, the drying temperature in step S12 is 60-80° C. and the drying time is 12-18 hours.

[0009] Preferably, the particle size of the recycled coarse aggregate is 5-40 mm.

[0010] Preferably, the preparation of modified graphene oxide comprises the following steps: S21. Add 1-5 parts of graphene oxide powder to 70-85 parts of deionized water and ultrasonically treat for 30-50 min to obtain a graphene oxide dispersion; S22. 4-6 parts of sodium borohydride powder are slowly added to the graphene oxide dispersion at a stirring speed of 400-500 r / min, and then reacted at a speed of 300-400 r / min for 2-4h in a water bath to obtain a modified mixed solution; S23. The modified mixed solution is centrifuged and washed with deionized water and alcohol for 3-5 times respectively, and centrifuged after each washing. After the last centrifugation, modified graphene oxide is obtained.

[0011] Preferably, the temperature of the water bath condition in step S22 is 40-60°C.

[0012] A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete, used for preparing the above-mentioned fiber-reinforced construction solid waste recycled aggregate concrete, comprises the following steps: S1. The recycled coarse aggregate, slag, fly ash and river sand are mixed and stirred in proportion to obtain a cement mixture; S2. The cement mixture obtained in step S1 is calcined for 2-3h to obtain cement clinker; S3. The cement clinker obtained in step S2, the modified fiber, the modified graphene oxide, and the tetrasodium iminodisuccinate were mixed in proportion, poured into a mixer and stirred for 5-6 min; S4. Add water into the mixer according to the proportion and continue stirring for 6-10 minutes before taking it out to obtain fiber-reinforced construction solid waste recycled aggregate concrete.

[0013] Preferably, the stirring speed in step S1 is 100-300 r / min, and the time is 7-10 min.

[0014] Preferably, in step S2, the calcination temperature is 800-1000°C.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention utilizes modified fibers to more closely connect polypropylene fibers to concrete. In the alkaline environment of concrete, it can undergo multiple reactions with components in concrete to form a stable network structure, thereby improving mechanical indicators such as the crack resistance and flexural strength of concrete.

[0016] 2. Recycled coarse aggregate has strong water absorption. During the hardening process of concrete, it can absorb excess water in the cement paste, reduce the porosity inside the concrete, and thus improve the concrete's impermeability and frost resistance. At the same time, due to the good bonding between recycled coarse aggregate and cement paste, it can effectively prevent the intrusion of harmful substances and enhance the durability of concrete.

[0017] 3. The conjugated structure of the modified graphene oxide in the present invention can effectively improve the conductivity and mechanical properties of concrete, making the fiber reinforcement effect better. The modified graphene oxide has a higher Young's modulus, can better withstand the stress inside the concrete, can also fill the pores in the concrete, enhance the density of the concrete, and promote the hydration reaction of cement, thereby improving the early strength of the concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a process flow chart for preparing fiber-reinforced construction solid waste recycled aggregate concrete; Figure 2 is a process flow chart of the preparation of the modified fiber of the present invention; Figure 3 The present invention is a process flow chart for preparing modified graphene oxide; Figure 4 This is a picture of the test piece of the fiber-reinforced construction solid waste recycled aggregate concrete after curing (used to test the mechanical properties); Figure 5 This is a picture of the test piece of the fiber-reinforced construction solid waste recycled aggregate concrete after curing (used for testing the durability, impermeability, frost resistance, and acid resistance). DETAILED DESCRIPTION

[0019] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] See also Figure 1-Figure 5 , the present invention provides a technical solution: Example 1 A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete S101. 15kg recycled coarse aggregate, 17kg slag, 30kg fly ash and 30kg river sand were mixed in proportion and stirred at a speed of 100r / min for 7min to obtain a cement mixture; S102. The cement mixture obtained in step S101 is calcined at 800° C. for 2 h to obtain cement clinker; S103. The cement clinker obtained in step S102, 1 kg of the modified fiber obtained below, 0.2 kg of the modified graphene oxide obtained below, and 1 kg of tetrasodium iminodisuccinate were mixed in proportion, poured into a mixer and stirred for 5 min; S104. Add 18 kg of water in proportion to the mixer and continue stirring for 6 min to obtain fiber-reinforced construction solid waste recycled aggregate concrete; In this embodiment, the preparation of the modified fiber includes the following steps: S10311. 1 kg of nano-silicon dioxide and 0.1 kg of sodium hexametaphosphate were added to 6 kg of anhydrous ethanol and ultrasonically treated for 30 min to obtain a nano-silicon dioxide dispersion; S10312. 1.5 kg of polypropylene fiber and 0.1 kg of γ-methacryloxypropyltrimethoxysilane were added to the nano-silicon dioxide dispersion, stirred at a speed of 700 r / min for 20 min, and then taken out and dried at 60° C. for 12 h to obtain a sufficient amount of modified fiber; The preparation of modified graphene oxide comprises the following steps: S10321. 0.1 kg of graphene oxide powder was added to 7 kg of deionized water and ultrasonically treated for 30 min to obtain a graphene oxide dispersion; S10322. 0.4 kg of sodium borohydride powder was slowly added to the graphene oxide dispersion at a stirring speed of 400 r / min, and then reacted at a speed of 300 r / min for 2 h in a 40° C. water bath to obtain a modified mixed solution; S10323. The modified mixed solution is centrifuged and washed with deionized water and alcohol three times respectively, and centrifuged after each washing. After the last centrifugation, a sufficient amount of modified graphene oxide is obtained.

[0021] Example 2 A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete S201. 20kg recycled coarse aggregate, 23kg slag, 35kg fly ash, 46kg river sand were mixed in proportion and stirred at a speed of 300r / min for 10min to obtain a cement mixture; S202. The cement mixture obtained in step S201 is calcined at 1000° C. for 3 h to obtain cement clinker; S203. The cement clinker obtained in step S202, 2.5 kg of the modified fiber obtained below, 1 kg of the modified graphene oxide obtained below, and 3 kg of tetrasodium iminodisuccinate were mixed in proportion, poured into a mixer and stirred for 6 min; S204. Add 23 kg of water in proportion to the mixer and continue stirring for 10 min to obtain fiber-reinforced construction solid waste recycled aggregate concrete; In this embodiment, the preparation of the modified fiber includes the following steps: S20311. 1.3 kg of nano-silicon dioxide and 0.3 kg of sodium hexametaphosphate were added to 8 kg of anhydrous ethanol and ultrasonically treated for 40 min to obtain a nano-silicon dioxide dispersion; S20312. 1.7 kg of polypropylene fiber and 0.3 kg of γ-aminopropyl triethoxysilane were added to the nano-silicon dioxide dispersion, stirred at a speed of 800 r / min for 25 min, and then taken out and dried at 80 ° C for 18 h to obtain a sufficient amount of modified fiber; The preparation of modified graphene oxide comprises the following steps: S20321. 0.5 kg of graphene oxide powder was added to 8.5 kg of deionized water and ultrasonically treated for 50 min to obtain a graphene oxide dispersion; S20322. 0.6 kg of sodium borohydride powder was slowly added to the graphene oxide dispersion at a stirring speed of 500 r / min, and then reacted at a speed of 400 r / min for 4 h in a 60° C. water bath to obtain a modified mixed solution; S20323. The modified mixed solution is centrifuged and washed with deionized water and alcohol for 5 times respectively, and centrifuged after each washing. After the last centrifugation, a sufficient amount of modified graphene oxide is obtained.

[0022] Example 3 A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete S301. 17kg recycled coarse aggregate, 20kg slag, 32kg fly ash and 35kg river sand were mixed in proportion and stirred at a speed of 200r / min for 8min to obtain a cement mixture; S302. The cement mixture obtained in step S301 is calcined at 900° C. for 2.5 h to obtain cement clinker; S303. The cement clinker obtained in step S302, 1.5 kg of the modified fiber obtained below, 0.5 kg of the modified graphene oxide obtained below, and 2 kg of tetrasodium iminodisuccinate were mixed in proportion and poured into a mixer and stirred for 5 min; S304. Add 20 kg of water in proportion to the mixer and continue stirring for 8 min to obtain fiber-reinforced construction solid waste recycled aggregate concrete; In this embodiment, the preparation of the modified fiber includes the following steps: S30311. 1.1 kg of nano-silicon dioxide and 0.2 kg of sodium hexametaphosphate were added to 7 kg of anhydrous ethanol and ultrasonically treated for 35 min to obtain a nano-silicon dioxide dispersion; S30312. 1.6 kg of polypropylene fiber and 0.2 kg of γ-methacryloxypropyltrimethoxysilane were added to the nano-silicon dioxide dispersion, stirred at a speed of 750 r / min for 22 min, and then taken out and dried at 70 ° C for 15 h to obtain a sufficient amount of modified fiber; The preparation of modified graphene oxide comprises the following steps: S30321. 0.3 kg of graphene oxide powder was added to 7.5 kg of deionized water and ultrasonically treated for 40 min to obtain a graphene oxide dispersion; S30322. 0.5 kg of sodium borohydride powder was slowly added to the graphene oxide dispersion at a stirring speed of 450 r / min, and then reacted at a speed of 350 r / min for 3 h in a 50° C. water bath to obtain a modified mixed solution; S30323. The modified mixed solution is centrifuged and washed with deionized water and alcohol for 4 times respectively, and centrifuged after each washing. After the last centrifugation, a sufficient amount of modified graphene oxide is obtained.

[0023] Example 4 A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete S401. 19kg recycled coarse aggregate, 22kg slag, 34kg fly ash, 45kg river sand were mixed in proportion and stirred at a speed of 250r / min for 9min to obtain a cement mixture; S402. The cement mixture obtained in step S401 is calcined at 950° C. for 2.5 h to obtain cement clinker; S403. The cement clinker obtained in step S402, 2 kg of the modified fiber obtained below, 0.8 kg of the modified graphene oxide obtained below, and 2.5 kg of tetrasodium iminodisuccinate were mixed in proportion and poured into a mixer and stirred for 6 min; S404. Add 22 kg of water in proportion to the mixer and continue stirring for 9 min to obtain fiber-reinforced construction solid waste recycled aggregate concrete; In this embodiment, the preparation of the modified fiber includes the following steps: S40311. 1.2 kg of nano-silicon dioxide and 0.2 kg of sodium hexametaphosphate were added to 7.5 kg of anhydrous ethanol and ultrasonically treated for 38 min to obtain a nano-silicon dioxide dispersion; S40312. 1.6 kg of polypropylene fiber and 0.2 kg of γ-aminopropyl triethoxysilane were added to the nano-silicon dioxide dispersion, stirred at a speed of 750 r / min for 24 min, and then taken out and dried at 75 ° C for 17 h to obtain a sufficient amount of modified fiber; The preparation of modified graphene oxide comprises the following steps: S40321. 0.4 kg of graphene oxide powder was added to 8 kg of deionized water and ultrasonically treated for 45 min to obtain a graphene oxide dispersion; S40322. 0.5 kg of sodium borohydride powder was slowly added to the graphene oxide dispersion at a stirring speed of 450 r / min, and then reacted at a speed of 350 r / min for 3 h in a 55° C. water bath to obtain a modified mixed solution; S40323. The modified mixed solution is centrifuged and washed with deionized water and alcohol for 4 times respectively, and centrifuged after each washing. After the last centrifugation, a sufficient amount of modified graphene oxide is obtained.

[0024] Comparative Example 1 A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete S501. 15kg recycled coarse aggregate, 17kg slag, 30kg fly ash and 30kg river sand were mixed in proportion and stirred at a speed of 100r / min for 7min to obtain a cement mixture; S502. The cement mixture obtained in step S501 is calcined at 800° C. for 2 h to obtain cement clinker; S503. The cement clinker obtained in step S502, 0.2 kg of the modified graphene oxide obtained below, and 1 kg of tetrasodium iminodisuccinate were mixed in proportion, poured into a mixer and stirred for 5 min; S504. Add 18 kg of water in proportion to the mixer and continue stirring for 6 min to obtain fiber-reinforced construction solid waste recycled aggregate concrete; In this comparative example, the preparation of modified graphene oxide comprises the following steps: S5031. 0.1 kg of graphene oxide powder was added to 7 kg of deionized water and ultrasonically treated for 30 min to obtain a graphene oxide dispersion; S5032. 0.4 kg of sodium borohydride powder was slowly added to the graphene oxide dispersion at a stirring speed of 400 r / min, and then reacted at a speed of 300 r / min for 2 h in a 40° C. water bath to obtain a modified mixed solution; S5033. The modified mixed solution is centrifuged and washed with deionized water and alcohol three times respectively, and centrifuged after each washing. After the last centrifugation, a sufficient amount of modified graphene oxide is obtained.

[0025] Comparative Example 2 A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete S601. 15kg recycled coarse aggregate, 17kg slag, 30kg fly ash and 30kg river sand were mixed in proportion and stirred at a speed of 100r / min for 7min to obtain a cement mixture; S602. The cement mixture obtained in step S601 is calcined at 800° C. for 2 h to obtain cement clinker; S203. The cement clinker obtained in step S602, 1 kg of the modified fiber obtained below, and 1 kg of tetrasodium iminodisuccinate were mixed in proportion and poured into a mixer and stirred for 5 min; S604. Add 18 kg of water in proportion to the mixer and continue stirring for 6 min to obtain fiber-reinforced construction solid waste recycled aggregate concrete; In this comparative example, the preparation of the modified fiber comprises the following steps: S6031. 1 kg of nano-silicon dioxide and 0.1 kg of sodium hexametaphosphate were added to 6 kg of anhydrous ethanol and ultrasonically treated for 30 min to obtain a nano-silicon dioxide dispersion; S6032. Add 1.5 kg of polypropylene fiber and 0.1 kg of γ-methacryloxypropyltrimethoxysilane into the nano-silica dispersion, stir at a speed of 700 r / min for 20 min, take out and dry at 60°C for 12 h to obtain a sufficient amount of modified fiber.

[0026] Performance Test: Compared with Example 1, Comparative Example 1 does not add modified fiber, and Comparative Example 2 does not add modified graphene oxide. The slag in Examples 1-4 and Comparative Examples 1-2 is granulated blast furnace slag, with a maximum particle size of ≤50mm and a specific surface area of ​​≥300m² / kg (S95 grade: specific surface area not less than 350m² / kg; S105 grade: specific surface area not less than 400m² / kg; S115 grade: specific surface area not less than 500m² / kg), and the average particle size DAV and the median particle size D50 (the cumulative volume fraction is 50%) are used. The particle size of powdered granular cementitious materials is described by the particle size of the corresponding particle size, among which the median particle size D50 is 11.86-68.05μm; the particle size of fly ash is less than or equal to 50μm; the particle size of nano-silicon dioxide is 20-40nm, and the average particle size is 20nm; the particle size of river sand is medium sand (Zone II), the fineness modulus is 3.0-2.3, the average particle size is 0.5-0.35mm, and the fineness modulus is 3.0-2.3. The specimens are placed on the bracket at a temperature of 18-22℃, a relative humidity of more than 95%, and the specimens are kept moist for curing. After the specimens are formed, they should be left to stand for 2 days in a room with a temperature of 15-25℃ and a relative humidity of more than 50%. During the standing period, they should be protected from vibration and impact. After standing, they should be numbered and marked, and the molds should be removed. If the specimens have serious defects, they should be disposed of as waste.

[0027] 1. Mechanical properties test According to the standard "GB / T 50081-2002 Standard for Test Methods of Mechanical Properties of Ordinary Concrete" and JC / T 2461 "Test Methods of Mechanical Properties of High-ductility Fiber-Reinforced Cement-Based Composite Materials", the fiber-reinforced construction solid waste recycled aggregate concrete prepared in the above Examples 1-4 and Comparative Examples 1-2 was cured for 28 days. Figure 1 The test pieces shown in the figure were subjected to performance tests, and the results are shown in Table 1 below: Table 1 ; It can be seen from the data in the table that the mechanical properties of the fiber-reinforced construction solid waste recycled aggregate concrete prepared in Comparative Examples 1-2 are inferior to those in Examples 1-4. The addition of modified fibers and modified graphene oxide can significantly improve the mechanical strength and toughness of the fiber-reinforced construction solid waste recycled aggregate concrete, and enhance its tensile strength, compressive strength and equivalent bending strength.

[0028] 2. Durability test According to GB / T 50082-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete, the specimens were alternately cycled in dry and wet environments to simulate the dry-wet changes of concrete in actual use. Each cycle includes: drying the specimen at 60°C for 24 hours, and then soaking it in 20°C water for 24 hours, and the number of cycles is 50 times. After 50 dry-wet cycles, the mass loss rates of the specimens of Examples 1-4 were 0.8%, 0.9%, 1.1%, and 1.0%, respectively, while the mass loss rates of Comparative Examples 1-2 were 1.5% and 1.6%, respectively. This shows that concrete mixed with modified fibers and modified graphene oxide has better durability.

[0029] 3. Impermeability test According to GB / T 50082-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete, the water pressure method is used to test the impermeability of concrete. Figure 5 The test piece is placed in a hydraulic pressure tester, and the water pressure starts from 0.1MPa and increases by 0.1MPa every 8 hours until the test piece seeps water, and the maximum water pressure value is recorded. The maximum water pressure values ​​of Examples 1-4 are 1.8MPa, 1.7MPa, 1.6MPa, and 1.7MPa, respectively, while the maximum water pressure values ​​of Comparative Examples 1-2 are 1.2MPa and 1.1MPa, respectively. This shows that the concrete mixed with modified fibers and modified graphene oxide has better anti-seepage performance.

[0030] 4. Freeze resistance test According to GB / T 50082-2009 Standard for test methods of long-term performance and durability of ordinary concrete, the attached Figure 5 The specimens were placed in a freeze-thaw tester and subjected to freeze-thaw cycles. Each cycle included freezing the specimens at -18°C for 4 hours and then thawing them in 20°C water for 4 hours, with a cycle number of 100 times. The mass loss rate and relative dynamic elastic modulus of the test specimens were tested. The mass loss rates of Examples 1-4 were 1.2%, 1.3%, 1.4%, and 1.3%, respectively, while the mass loss rates of Comparative Examples 1-2 were 2.5% and 2.6%, respectively, indicating that concrete mixed with modified fibers and modified graphene oxide has better frost resistance.

[0031] 5. Acid resistance According to GB / T 50082-2009 Standard for test methods of long-term performance and durability of ordinary concrete, the attached Figure 5 The specimens were immersed in 5% hydrochloric acid, sulfuric acid and nitric acid solutions for 150 days, and the mass loss rate and compressive strength changes of the specimens were tested. The mass loss rates of Examples 1-4 in hydrochloric acid, sulfuric acid and nitric acid were 1.5%, 1.6% and 1.7% respectively, while the mass loss rates of Comparative Examples 1-2 were 3.2% and 3.3% respectively. This shows that concrete mixed with modified fibers and modified graphene oxide has better acid resistance.

[0032] 6. Early compressive strength performance test According to GB / T 50081-2002 Standard for Test Methods of Mechanical Properties of Ordinary Concrete, the compressive strength of the fiber-reinforced construction solid waste recycled aggregate concrete prepared in Examples 1-4 and Comparative Examples 1-2 was tested after curing for 3d, 7d, and 28d. The results are shown in Table 2 below: Table 2 ; The data show that concrete mixed with modified fibers and modified graphene oxide is significantly better than concrete without any additions in terms of early strength development, especially in terms of early strength at 3 days and 7 days.

[0033] The recycled coarse aggregate in the present invention has strong water absorption. During the concrete hardening process, it can absorb excess water in the cement slurry and reduce the porosity inside the concrete, thereby improving the concrete's impermeability and frost resistance. In addition, due to the good bonding between the recycled coarse aggregate and the cement slurry, it can effectively prevent the intrusion of harmful substances and enhance the durability of the concrete.

[0034] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fiber-reinforced construction solid waste recycled aggregate concrete, characterized in that: The invention comprises the following components in parts by mass: 150-200 parts of recycled coarse aggregate, 170-230 parts of slag, 300-350 parts of fly ash, 180-230 parts of water, 10-25 parts of modified fiber, 2-10 parts of modified graphene oxide, 300-460 parts of river sand and 10-30 parts of tetrasodium iminodisuccinate.

2. The fiber-reinforced construction solid waste recycled aggregate concrete according to claim 1, characterized in that: The preparation of the modified fiber comprises the following steps: S11. 10-13 parts of nano-silicon dioxide and 1-3 parts of sodium hexametaphosphate are added to 60-80 parts of anhydrous ethanol and ultrasonically treated for 30-40 min to obtain a nano-silicon dioxide dispersion; S12. Add 15-17 parts of polypropylene fiber and 1-3 parts of organic silane coupling agent to the nano-silicon dioxide dispersion, stir at a speed of 700-800 r / min for 20-25 min, take out and dry to obtain modified fiber.

3. The fiber-reinforced construction solid waste recycled aggregate concrete according to claim 2, characterized in that: The organic silane coupling agent is one of γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

4. The fiber-reinforced construction solid waste recycled aggregate concrete according to claim 2, characterized in that: The drying temperature in step S12 is 60-80° C. and the drying time is 12-18 hours.

5. The fiber-reinforced construction solid waste recycled aggregate concrete according to claim 1, characterized in that: The particle size of the recycled coarse aggregate is 5-40 mm.

6. The fiber-reinforced construction solid waste recycled aggregate concrete according to claim 1, characterized in that: The preparation of the modified graphene oxide comprises the following steps: S21. Add 1-5 parts of graphene oxide powder to 70-85 parts of deionized water and ultrasonically treat for 30-50 min to obtain a graphene oxide dispersion; S22. 4-6 parts of sodium borohydride powder are slowly added to the graphene oxide dispersion at a stirring speed of 400-500 r / min, and then reacted at a speed of 300-400 r / min for 2-4h in a water bath to obtain a modified mixed solution; S23. The modified mixed solution is centrifuged and washed with deionized water and alcohol for 3-5 times respectively, and centrifuged after each washing. After the last centrifugation, modified graphene oxide is obtained.

7. The fiber-reinforced construction solid waste recycled aggregate concrete according to claim 6, characterized in that: The temperature of the water bath condition in step S22 is 40-60°C.

8. A method for preparing fiber-reinforced construction solid waste recycled aggregate concrete, used for preparing the fiber-reinforced construction solid waste recycled aggregate concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. The recycled coarse aggregate, slag, fly ash and river sand are mixed and stirred in proportion to obtain a cement mixture; S2. The cement mixture obtained in step S1 is calcined for 2-3h to obtain cement clinker; S3. The cement clinker obtained in step S2, the modified fiber, the modified graphene oxide, and the tetrasodium iminodisuccinate were mixed in proportion, poured into a mixer and stirred for 5-6 min; S4. Add water into the mixer according to the proportion and continue stirring for 6-10 minutes before taking it out to obtain fiber-reinforced construction solid waste recycled aggregate concrete.

9. The method for preparing fiber-reinforced construction solid waste recycled aggregate concrete according to claim 8, characterized in that: The stirring speed in step S1 is 100-300 r / min, and the stirring time is 7-10 min.

10. The method for preparing fiber-reinforced construction solid waste recycled aggregate concrete according to claim 8, characterized in that: In step S2, the calcination temperature is 800-1000°C.

Citation Information

Patent Citations

  • Oxidized graphene and graphene reinforced cement based composite material and preparation method thereof

    CN103130436A

  • Alkali-activated fly ash / slag recycled concrete and preparation method thereof

    CN112250355A

  • Basalt fiber concrete with ultrahigh mechanical property as well as preparation method and application of basalt fiber concrete

    CN116120029A

  • Surface-modified steel fiber, modification method and concrete based on steel fiber

    CN117800641A

  • Green low-carbon recycled concrete material as well as preparation method and application thereof

    CN119038938A

Cited By

  • High-strength and high-toughness gold tailing-based foam light soil as well as preparation method and application thereof

    CN120328989A

  • A high-strength and high-toughness gold tailings-based foamed lightweight soil and its preparation method and application

    CN120328989B

  • Fiber reinforced concrete based on building solid waste recycled aggregate and preparation method thereof

    CN120463454A

  • Recycled aggregate-fiber composite ecological concrete and preparation method thereof

    CN122403894A